Effects of chemotherapy and immunotherapy on microbial diversity in TME and engineered bacterial-mediated tumor therapy - Zheng, Heng; Chen, Xianxian; Li, Qiyang; Liu, Yuqi; Cai, Jinzhong (Frontiers in Immunology, 2023)
Tumor microbiota is a group of microorganisms located in tumor tissues with rich diversity that can promote tumorigenesis and development, and different types of tumors have different tumor microbiotas, which has important implications for tumor research, detection, and clinical treatment. In this review, we examine the diversity of the tumor microbiota, discuss the impact of chemotherapy and immunotherapy on tumor microbiota diversity, and summarize recent advances in the use of genetically engineered bacteria for the treatment of tumors. In addition, we propose key questions that need to be further addressed by the tumor microbiota.